Development of Entrepreneurship Training Model of "Smart Entrepreneur Model" (SEM) at the Universitas Negeri Padang - Asmar Yulastri (JURNAL PENDIDIKAN DAN KELUARGA, 2020)
Training Entrepreneurship is one of the efforts to streamline the purpose of supporting entrepreneurship education in universities. This study aims to develop and produce a model of entrepreneurship training of "Smart Entrepreneur Model" (SEM) developed by using Four D's approach. The design development of the SEM Model Training Model was using ADDIE Instructional Design. Results of the research on the stages of needs analysis showed that students have a very high requirement for learning entrepreneurship, entrepreneurial planning, and business management, as well as a high need for a training online business based. Rationalization development carried out was a matter of lack of funded proposals by Ditjen which were only 21.42% of the submitted proposals which met the criteria set forth. Then, from 81 funded business proposals, it was only 30.86% that run caused by weak of business management committed by participants of Students Entrepreneurial Program (PMW). In the development of SEM Training Model, the design is Needs Analysis stage and skills gap analysis. Stages of the design were based on objectives, performance, goals of activities, methods, place and time, content, and syntax. Developed Syntax of SEM consisted of 8 steps of training activities where Syntac of SEM training Model consisted of the 8-step training process. They are Preparation Participants Training, Psychometric Test, Identification Results of Psychometric Tests, Analysis of Business, Management Mentoring, Mentoring Online Business, Business progress report, Evaluation of training implementation.